(untitled) (Revista de História Regional, 2007)
The article deals on the ways Auguste de Saint-Hilaire, French voyager, gazed upon the Campos Gerais, as he rode through the region in 1820. The work is based on the semiologic analysis of speech, according to Roland Barthes. This analytical focus is centered at some specific moments in the voyagers vision: nature, the production of material life, with emphasis in cattle raising, characteristic of the region; and the cultural and social dimension of the region in its different aspects (cities, buildings, people, art, etc.). The Campos Gerais are privileged in this approach because they were, to Saint-Hilaire, a qualitatively superior dimension, as compared to other regions of the country seen by him, even when he is mostly stranged an enchanted by the region. The comparison between the scientific strictness and neutrality of the botanic and the enchantment of the man run through this work. The analysis is made on a speech founded in the European standard of values, which defines absolute truth and the consequent distance and awe in face of the difference of the society in the Campos Gerais at the time.